Financial Independence of a Public Hospital as Regional Public Service Body During COVID-19 Pandemic - Rita Damayanti; Dominggus Paliling; Yudi Hartono; Wulan I. R. Sari; Cornelius Rantelangi; Dwi R. Deviyanti (Journal of International Conference Proceedings (JICP), 2022)
The continuity of quality health services supported by financial independence is the focus of research. Whether during the COVID-19 pandemic, public hospitals could be financially independent is an important question for this research. Study aims to assess the financial independence at public hospital as the regional public service body (BLUD) during COVID-19. This study uses a comparative descriptive approach by comparing data before and during the COVID-19 pandemic. The secondary data used are financial reports, patient visit data, and reports on the results of the community satisfaction index (IKM) survey from the Public Hospital AM. The results show that financial independence and community satisfaction for services have better impact to public hospital during COVID-19. Although patients gave a satisfied assessment of health services, the pandemic period had a negative impact on decreasing patient visits. In short, the decreasing number of patients does not affect financial independence and the quality of health services in public hospitals, on the contrary, it increases. This means that there is an increase in income from other sources that are not directly related to health services.Keywords: Community Satisfaction Index, COVID-19 Pandemic, Financial Independence, Health Services, Public Hospital, Public Service Body, Quality of Services.